Synthesis of Polycyclic Aromatic Hydrocarbons by Phenyl Addition–Dehydrocyclization: The Third Way. (16th October 2019) - Zhao, Long; Prendergast, Matthew B.; Kaiser, Ralf I.; Xu, Bo; Ablikim, Utuq; Ahmed, Musahid; Sun, Bing‐Jian; Chen, Yue‐Lin; Chang, Agnes H. H.; Mohamed, Rana K.; Fischer, Felix R.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) represent the link between resonance‐stabilized free radicals and carbonaceous nanoparticles generated in incomplete combustion processes and in circumstellar envelopes of carbon rich asymptotic giant branch (AGB) stars. Although these PAHs resemble building blocks of complex carbonaceous nanostructures, their fundamental formation mechanisms have remained elusive. By exploring these reaction mechanisms of the phenyl radical with biphenyl/naphthalene theoretically and experimentally, we provide compelling evidence on a novel phenyl‐addition/dehydrocyclization (PAC) pathway leading to prototype PAHs: triphenylene and fluoranthene. PAC operates efficiently at high temperatures leading through rapid molecular mass growth processes to complex aromatic structures, which are difficult to synthesize by traditional pathways such as hydrogen‐abstraction/acetylene‐addition. The elucidation of the fundamental reactions leading to PAHs is necessary to facilitate an understanding of the origin and evolution of the molecular universe and of carbon in our galaxy. Abstract : Sternenstaub : Die Triphenylen‐ und Fluoranthen‐Moleküle – mögliche Vorstufen zu zwei‐ und dreidimensionalen graphitischen Nanoblättchen im interstellaren Raum – können durch rasche Molekülmassen‐Wachstumsprozesse infolge der Reaktion des Phenylradikals mit Biphenyl bzw. Naphthalin bei hohen Temperaturen gebildet werden.